The Histone Methyltransferase MMSET/WHSC1 Activates TWIST1 to Promote an Epithelial-Mesenchymal Transition and Invasive Properties of Prostate Cancer - Ezponda, Teresa (2012)
Epigenetic deregulation of gene expression plays a role in the initiation and progression of prostate cancer (PCa). The histone methyltransferase MMSET/WHSC1 (Multiple Myeloma Set Domain) is overexpressed in a number of metastatic tumors, but its mechanism of action has not been defined. In this work, we found that PCa cell lines expressed significantly higher levels of MMSET compared to immortalized, non-transformed prostate cells. Knockdown experiments showed that, in metastatic PCa cell lines, dimethylation of lysine 36 and trimethylation of lysine 27 on histone H3 (H3K36me2 and H3K27me3, respectively) depended on MMSET expression, while depletion of MMSET in benign prostatic cells did not affect chromatin modifications. Knockdown of MMSET in DU145 and PC-3 tumor cells decreased cell proliferation, colony formation in soft agar, and strikingly diminished cell migration and invasion. Conversely, overexpression of MMSET in immortalized, non-transformed RWPE-1 cells promoted cell migration and invasion, accompanied by an epithelial to mesenchymal transition (EMT). Among a panel of EMT-promoting genes analyzed, TWIST1 expression was strongly activated in response to MMSET. Chromatin immunoprecipitation analysis demonstrated that MMSET binds to the TWIST1 locus, leading to an increase in H3K36me2, suggesting a direct role of MMSET in the regulation of this gene. Depletion of TWIST1 in MMSET-overexpressing RWPE-1 cells blocked cell invasion and EMT, indicating that TWIST1 was a critical target of MMSET, responsible for the acquisition of an invasive phenotype. Collectively, these data suggest that MMSET plays a role in PCa pathogenesis and progression through epigenetic regulation of metastasis-related genes.